Screening for Methicillin-Resistant Staphylococcus spp. Dog Isolates Capable of Transferring mecA - Brost, Allison; Schauer, Courtney; Showsh, Sasha A. (My University, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) is an antibiotic-resistant strain of the bacterium Staphylococcus aureus that is responsible for many community and hospital-acquired infections worldwide. A survey of the dogs at the local Veterinary Hospital was conducted to indicate the relative presence of Methicillin-Resistant Staphylococcus spp. (donor strains). We used Mannitol Salt Agar (MSA) with oxicillin (4μg/ml) to collect 67 bacterial samples from 39 dogs. Of these, 38 samples displayed characteristics of MRSA and were designated as potential methicillin-donors. PCR analysis however, determined only one of these donors to be MRSA while the rest appear to be other staphylococcal species. In addition, the MRSA isolate was determined to contain plasmid. All the donors were screened for their ability to transfer the methicillin-resistance gene (mecA) to a methicillinsensitive, streptomycin and spectinomycin resistant Staphylococcus aureus recipient (SAS 850). To determine the ability of the isolates to transfer the mecA gene, a series of conjugation experiments were conducted with potential donors and recipient. The resulting transconjugants (S. aureus SAS850 with methicillin resistance) were selected for on Columbia Blood Agar (CBA) plates containing streptomycin, spectinomycin, and oxicillin. Oxicillin resistant transconjugants were analyzed by PCR and coagulase test to determine the samples to be S. aureus. To date, 28 of the 38 donor strains have been tested and we have not been able to detect the transfer of mecA.
Color poster with text, charts, and diagrams.
Keywords: Staphylococcus aureus; MRSA; Antibiotic resistance; Posters